Strategies for Improving Digital Literacy Through The Use of Digital Technology by Small and Medium Enterprises Assisted by The Cooperative and SME Service Office of Yogyakarta Special Region - Dinda Artya Hamidah (PT SOLUSI EDUKASI BERDIKARI, 2024)
The rise of digital trends and information technology brings new opportunities and challenges for SMEs. The use of digital technology is important for company growth, but SMEs often struggle to adopt it due to a lack of understanding of digital literacy. In the era of digitalization, businesses need to choose and make optimal use of digital technology, such as the SiBakul Jogja application that can expand markets and accelerate business development. This study uses a quantitative descriptive method with 69 respondents and applies the Technology Acceptance Model (TAM) which considers aspects of usability and ease of use of the SiBakul Jogja application. Meanwhile, external variables such as user attitude, user interest, and actual use were also added for digital technology in general. The results of the TAM analysis show the level of acceptance of business actors towards SiBakul Jogja technology and help formulate strategies to increase the adoption of digital technology.